Digital Death, Digital Assets and Post-mortem Privacy : Theory, Technology and the Law - Harbinja, Edina (Future Law : FULA, 2022)
Addresses the fundamental questions of how our data, online identity and digital assets are treated after deathExamines aspects of property, intellectual property, contract, succession and probate, privacy and data protection, jurisdiction and criminal law Develops a new concept of postmortal privacy Draws on 3 cases studies: the transmission of emails, online games such as World of Warcraft and social networks as the most typical, prominent and widely used types of assets Puts forward policy suggestions, proposals for law reforms and sets out an innovative agenda which will open new avenues for research Offers practical advice for the legal profession and users Edina Harbinja examines the theoretical, technological and doctrinal issues surrounding online death and digital assets. By examining different areas of law, humanities and social science, she proposes the new concept of postmortal privacy (privacy of the deceased individuals) and provides answers and suggestions as to what happens to digital assets and online identity after death. Case studies draw on the transmission of emails, online games such as World of Warcraft and social networks to examine the legal issues surrounding these most prominent and widely used types of assets. Aspects of property, intellectual property, contract, succession and probate, privacy and data protection, jurisdiction and criminal law are considered. Harbinja puts forward policy suggestions, proposals for law reforms and sets out an innovative agenda which will open new avenues for research. Her useful consideration of current digital legacy tools and technologies also offers practical advice for users when it comes to their own estate planning.